2018
DOI: 10.1016/j.juro.2017.11.048
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Study of Bladder Continence in Patients with Spina Bifida in the National Spina Bifida Patient Registry

Abstract: Purpose Achieving bladder continence in individuals with spina bifida is a lifetime management goal. We investigated bladder continence status through time and factors associated with this status in patients with spina bifida. Materials and Methods We used National Spina Bifida Patient Registry data collected from 2009 through 2015 and applied generalized estimating equation models to analyze factors associated with bladder continence status. Results This analysis included 5,250 participants with spina bif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 19 publications
(21 reference statements)
0
28
0
Order By: Relevance
“…MMC was the most common diagnosis (81.5%; Thibadeau, ). From the inception of the NSBPR, there have been challenging issues in the interpretation of some particular registry variables (e.g., differences across sites in definitions bowel and bladder continence); thus, as the registry has evolved, the enquiry points have been refined and expanded (Liu et al, ). Accordingly, there has been a focus on detection of variations in care across registry centers providing an opportunity for several centers to evaluate outcomes related to treatments.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…MMC was the most common diagnosis (81.5%; Thibadeau, ). From the inception of the NSBPR, there have been challenging issues in the interpretation of some particular registry variables (e.g., differences across sites in definitions bowel and bladder continence); thus, as the registry has evolved, the enquiry points have been refined and expanded (Liu et al, ). Accordingly, there has been a focus on detection of variations in care across registry centers providing an opportunity for several centers to evaluate outcomes related to treatments.…”
Section: Resultsmentioning
confidence: 99%
“…Liu et al () reported on the status of bladder continence through time and its associated factors. At last follow‐up, 22.4% of participants had undergone surgery for bladder continence and 45.8% reported bladder continence.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations